Performance of crosses and development of doubled haploid lines in wheat (Triticum aestivum L.) for salt tolerance - Abdulrahman, Abbas Lateef (2018)
Wheat (Triticum aestivum L.) is an important staple food crop for the world population. Despite its importance, the crop productivity is often affected by salinity stress. This study aimed to develop sodium chloride (NaCl) tolerant doubled haploid wheat using anther culture technique. The effect of different concentrations of NaCl (0, 50, 100, 150 and 250 mM) on seed germination and selected seedling growth traits of eight wheat genotypes was evaluated. The G1, G2, G6, G8, and G10 were classified as salt tolerant while Abo- Graib, Forat and, Dijla genotypes were salt susceptible. Increasing concentration of NaCl solution led to the gradual reduction in the seed germination percentage, and seedling growth traits. The three salt susceptible and one high salt tolerant genotypes (G8) were selected for crossing to obtain a total of six crosses. The agronomic performance of the six F1 crosses was investigated under 0, 50, 100, 150 mM of NaCl. For all, grain yield exhibited positive correlation with spikes number/plant, grains number per spike and weight of 1000 grain. Abo- Graib×G8, Forat×G8, and Dijla×G8 showed superiority in grain yield (7.3 g/plant, 7.4 g/plant and 6 g/plant, respectively) under high concentration of NaCl (100 mM) related to the spikes number/plant, grains number per spike and the 1000 grain weight. Investigation on callus induction from anther culture of the F1 progenies was performed. All F1 produced a high percentage of callus (47.9%) when subjected to 33°C + chemical pre-treatment for 48 hours followed by culturing on CHB3 induction medium containing Myo-inositol (300 mg/L), L-glutamine (993.5 mg/L) and 2 mg/L of both 2, 4-D and kinetin. The F1 produced good percentage (45.6%) of green plants and the lowest percentage (6.8%) of albino plants after growing on R9 regeneration medium containing 0.076 mg/L CuSO4.5H2O and 90000 mg/L maltose following the pre-treatment of the anther with heat + chemical and culturing on CHB3 callus induction medium. Abo-Graib×G8 displayed the highest ability for callus induction and green plants production (82.3% and 81.3%, respectively) and the lowest percentage of albino plants (2%). The 883 regenerated plants from the F1, 646 were green and 237 were albino plants. Among the green plants, 281 grew to maturity. Thirty-nine lines were fertile and their seeds were grown for developing salt tolerant doubled haploid lines. Haploid plant's chromosomes were doubled under colchicine treatment (0.2%) with dimethyl sulfoxide (DMSO) (2%) and 2-3 drops of Tween-20 for 4 hours at room temperature. The doubling of chromosomes was validated using a fluorescent microscope. Thirty-nine doubled haploid lines were evaluated under 0, 50, 100 and 150 mM of NaCl in the greenhouse. The doubled haploid lines DH6 obtained from (Abo-Graib×G8), DH8 (Forat×G8) and DH6 (Dijla×G8) showed a high performance due to their superiority in leaves K+ content, K+/Na+ ratio, the spikes number, grains number, and the decrease in leaves Na+ content. Taken together, it can be concluded that through anther culture, doubled haploid lines that displayed high yielding trait were developed for future exploitation.